Effect of Cation Distribution on Structural and Magnetic Properties of Nickel Cobalt Zinc Ferrites. (27th October 2013) - Azhagushanmugam, S. J.; Suriyanarayanan, N.; Jayaprakash, R.
Abstract : Nanoparticles of Ni(0.8− x ) Co(0.2) Zn( x ) Fe2 O4 (x = 0.2, 0.4, and 0.6) are prepared by chemical coprecipitation method. Effects of zinc substitution on structural and magnetic properties have been investigated. The X-ray diffraction and infrared spectroscopy are used to characterize the samples. The XRD pattern of the samples provides evidence of single phase formation of spinel structure with cubic symmetry. It is observed that the particle size decreases and lattice parameter increases with the increase in zinc concentration. TEM micrographs show a well-defined nanocrystalline state with an average particle size of around ≈ 17 nm. The B-H loops of all samples that are obtained by using vibrating sample magnetometer are displayed. The effect of Zn addition on saturation magnetization and the coercivity of all the samples are discussed.